Evaluating the impact of hierarchical deep-water slope channel architecture on fluid flow behavior, Cretaceous Tres Pasos Formation, Chile - Ruetten, Andrew, author; Stright, Lisa, advisor; Ronayne, Michael, committee member; Bailey, Ryan, committee member (Colorado State University. Libraries, 2021)
Channelized deep-water reservoirs inherently contain sub-seismic scale heterogeneity, resulting in uncertainty when evaluating reservoir connectivity and flow patterns. Stratigraphic architectural features, including stacked channel elements, channel element fill, mass transport deposits (MTDs), and channel base drapes, can have a complex and significant impact on fluid flow pathways. While this detailed stratigraphic architecture can be difficult to capture at the development scale, it can be effectively modeled at the sector scale using high-resolution outcrop data. The characterization of flow behaviors and reservoir performance at this finer scale can then be used in the construction of lower-resolution development-scale simulations. This study uses a three-part sensitivity analysis to test how fluid flow behavior responds to channel element stacking patterns, net to gross ratio, channel base drape coverage, and MTD properties. First, simplified models are used to isolate key flow behaviors. Then, field data is incorporated from the seismic-scale Laguna Figueroa outcrop of the Cretaceous Tres Pasos Formation, Magallanes Basin, Chile to construct a deterministic outcrop model that incorporates realistic stacking patterns and architectural features, including MTDs. Finally, stochastic object-based methods are used to try to replicate the flow characteristics of the outcrop model using established geostatistical methods and limited data input. Fluid flow was simulated using a constant flux aquifer at the base of the model and three producing wells at the top, and the results of the three modeling methods were compared in an effort to elucidate key flow behaviors.
Keywords: flow simulation; deep-water channels; geocellular modeling